Privatization and labor: what happens to workers when governments divest? - Kikeri, Sunita; The World Bank (Washintong, D.C The World Bank, 1998)
This book investigates the reaction by the labor when government deviate or pull out it resources from enterprise business for the sake of privatization.
This publication is a work in progress for public discussion
Includes bibliography
mf 21/01/2019
Loans
Keywords: Government business enterprises-developing countries; privatization